Correlation between endothelial CXCR7 expression and clinicopathological factors in oral squamous cell carcinoma. Issue 6 (30th March 2021) - Yanagiya, Misa; Dawood, Randa I. H.; Maishi, Nako; Hida, Yasuhiro; Torii, Chisaho; Annan, Dorcas A.; Kikuchi, Hiroshi; Yanagawa Matsuda, Aya; Kitamura, Tetsuya; Ohiro, Yoichi; Shindoh, Masanobu; Tanaka, Shinya; et al.
Abstract : Oral squamous cell carcinoma (OSCC) impairs functionality and sensuousness resulting in poor quality of life. Biomarkers can predict disease trajectory and lead to effective treatments. Transcriptomics have identified genes that are upregulated in tumor endothelial cells (TECs) compared with normal endothelial cells (NECs). Among them, chemokine receptor 7 (CXCR7) is highly expressed in TECs of several cancers and involved in angiogenesis of TECs. However, levels of CXCR7 in OSCC blood vessels have not been fully investigated. In this study, we analyzed the correlation between CXCR7 expression in TECs and clinicopathological factors in OSCC. Immunohistochemistry for CXCR7 and CD34 was performed on 59 OSCC tissue specimens resected between 1996 and 2008 at Hokkaido University Hospital. CXCR7 expression in blood vessels was evaluated by the ratio of CXCR7+/CD34+ blood vessels. CXCR7 expression was 42% and 19% in tumor and non‐tumor parts, respectively, suggesting that CXCR7 expression is higher in TECs than in NECs. CXCR7 expression in TECs correlated with advanced T‐stage and cancer stage. Overall survival and disease‐free survival rates were higher in low‐expressing CXCR7 patients than in high‐expressing. These results suggest that CXCR7 expression in blood vessels may be a useful diagnostic and prognostic marker for OSCC patients.